Learning Plan with Blended learning in Elemetary School - Panjaitan, Retna; Murniarti, Erni; Sihotang, Hotmaulina (Advances in Social Sciences Research Journal, 2021)
Information and communication technology in the education world during the Covid-19 era played an extremely important role. Everything can be easily done without any limit because each individual can do it himself. Technology is giving new colors and faces to education systems in all parts of the world today. This is evidenced by the development of many learning models that refer to independent learning based on information technology. The purpose of this paper is to develop a blended learning model for thematic learning in elementary schools according to the needs of learning activities. This development method refers to the Dick, Carey (2009:6-7), development model and adapts the Blended learning model. The application of the blended learning model refers to the curriculum that is being used during the Covid-19 pandemic, namely the 2013 curriculum which is simplified independently in elementary school.